The Removal Of Oil From Oil-In-Water Emulsions By Modified Kapok Fiber With Hydrochloric Acid - Lee, Li Ying (Universiti Sains Malaysia, 2022)
Kapok fiber is widely used in oil absorption as it offers many benefits such as excellent oil absorption capacity, biodegrability, reusability, abundancy and low cost. The treatment of kapok fiber with hydrochloric acid (HCl) arises to enhance the absorption of oil. Hence, this research work targeted to generate modified kapok fiber with HCl solution. In this study, kapok fiber was synthesized at an optimized HCl concentration, treatment temperature and treatment time. With the modified kapok fiber, 94.90% of oil removal from oil-in-water emulsions was reached at an initial oil concentration of 1000 ppm. The separation efficiency was improved with increasing of HCl concentration, treatment temperature and treatment time. This was due to the enhancement of crystalline packing and surface roughness of kapok fiber. However, when these parameters increased beyond their optimum values which are 1.5%, 70 °C and 50 minutes, the performance of kapok fiber dropped because of the damaged kapok structure under extreme conditions. The absorption capacity of modified kapok fiber was also improved by decreasing the initial oil concentration due to larger surface area for absorbing oil remained. The results proved that kapok fiber is a promising absorbent to remove oil from oil-in-water emulsion in industrial wastewater.